Correlation between Enthusiasm Level and Entrepreneurial Personality - Rahman, Vina Tri Agustiani; Rukmana, Endris; Ramdhan, Billyardi (Jurnal Report of Biological Education, 2024)
Background: Entrepreneurship education plays a crucial role in developing students' entrepreneurial potential. Two significant aspects of this education are Enthusiasm Level and Entrepreneurial Personality. This study aims to examine the correlation between students' Enthusiasm Level and Entrepreneurial Personality in the implementation of the entrepreneurial-based Project for Strengthening Pancasila Student Profile (P5) at a high school in Sukabumi Regency. Method: Using a descriptive qualitative approach, data were collected through a questionnaire consisting of 44 statements and in-depth interviews with teachers.  Results: The results showed that the implementation of the P5 Project had a positive impact on students' enthusiasm and Entrepreneurial Personality. Pearson correlation test indicated a very weak positive relationship between Enthusiasm Level and Entrepreneurial Personality with a correlation coefficient of 0.117 and significance of 0.041. Although this relationship is significant, its strength is very low, suggesting that other factors may have a greater influence on the development of Entrepreneurial Personality. Conclusion:  This research provides insights into the importance of creating a supportive learning environment to enhance students' enthusiasm and Entrepreneurial Personality. Keywords : Project to Strengthen Pancasila Student Profiles (P5), Enthusiasm Level, Entrepreneurial Personality, independent curriculum, entrepreneurship education